Comparison of Echocardiographic Patterns between Mild to Moderate and Severe CKD with type 4 Cardio renal Syndrome Patients - Banerjee, Sajal K; Zaman, SM Mustafa; Ghosh, Rajesh K; Hoque, Harisul (University Heart Journal, 2016)
Abstract not available University Heart Journal Vol. 11, No. 1, January 2015; 02